Nitrogen and Sulfur Fertilization’s Effect on Soybean Quality and Yield in Kansas - Yuri A. B. Gross; Luiz Felipe A. Almeida; Ignacio Antonio Ciampitti (Kansas Agricultural Experiment Station Research Reports, 2024)
This study evaluates the effects of nitrogen (N) and sulfur (S) fertilization on soybean yield and quality. Over three years (2021-2023), nine site-year studies in Kansas tested five fertilization strategies, including Check (no fertilization), S (30.3 lbs S ac-1), N (26.8 lbs N ac-1), NS (26.8 lbs N ac-1 + 30.3 lbs S ac-1), and Full (30.3 lbs S ac-1 + 299.8 lbs N ac-1). Seed yield was recorded, and the seeds were analyzed for protein content. Weather data was summarized into four growth periods. There were no yield or protein content differences. Seed yield and protein showed positive correlation with soil-N content, and with precipitation and average temperature from flowering to full-pod phenological stage. The study suggests that current N2-fixation and soil-N contributions are adequate for optimal growth, pointing toward the importance of site-specific management.
Keywords: soybean; protein; yield; sulfur; nitrogen